The sharp bound of the third Hankel determinant for certain subfamilies of analytic functions - Rath, Biswajit; Kumar, K. Sanjay; Krishna, D. Vamshee; Viswanadh, G. K. Surya (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 We study an upper bound and the sharp bound of the third-order Hankel determinant for some subfamilies of analytic functions for the parameters α(1,4/3] and α=3/2, respectively, also proving the recent conjecture for the sharp bounds made in [Virendra Kumar, Sushil Kumar, V. Ravichandran, Third Hankel determinant for certain classes of analytic functions, Mathematical Analysis I: Approximation Theory, February (2020); DOI: 10.1007/978-981-15-1153-019].